The relationship between social anxiety levels and effective communication skills of adolescents participating in sports - Alev Üstündağ; Semanur Haydaroğlu; Dilara Sayan; Merve Güngör (Scientific Reports)
Abstract The present study examines the relationship between social anxiety levels and effective communication skills in adolescents engaged in sports. The correlational study was conducted with 352 voluntary adolescents aged 15 to 18 enrolled in a sports high school. Data were collected using a personal information form, the Social Anxiety Scale for Adolescents (SAS-A), and the Communication Skills Scale (CSS). A comprehensive data analysis approach encompassing descriptive statistics, independent samples t-test, one-way ANOVA, Tukey post hoc test, Pearson correlation analysis, and point-biserial correlation analysis was employed to systematically examine the data. The ensuing results are as follow: the study yielded several significant findings First, female adolescents exhibited higher levels of social anxiety compared to their male counterparts. Secondly, a significant, positive, and strong relationship was identified between adolescents’ fear of negative evaluation, social avoidance and distress in general situations, social avoidance and distress in new situations, and overall social anxiety levels. Thirdly, the study found that adolescents’ social anxiety levels were found to be a significant predictor of their communication skills, indicating that as social anxiety levels increased, communication skills decreased. These findings collectively suggest that social anxiety exerts a substantial negative impact on adolescents’ communication skills.